2007
DOI: 10.1161/strokeaha.107.481788
|View full text |Cite
|
Sign up to set email alerts
|

Iron Oxide Particle-Enhanced MRI Suggests Variability of Brain Inflammation at Early Stages After Ischemic Stroke

Abstract: Background and Purpose-Inflammation contributes to brain damage caused by ischemic stroke. Ultrasmall superparamagnetic iron oxide (USPIO)-enhanced MRI allows noninvasive monitoring of macrophage recruitment into ischemic brain lesions. In this study, we determined the extent of USPIO enhancement during early stages of ischemic stroke. Methods-Twelve consecutive patients with typical clinical signs of stroke underwent multimodal stroke imaging at 1.5-T within 24 hours of symptom onset. They received intravenou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
88
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(89 citation statements)
references
References 27 publications
0
88
0
1
Order By: Relevance
“…Recently, several studies have reported the use of magnetic nanoparticles to identify inflammatory regions in stroke (4,(23)(24)(25). However, magnetic nanoparticles detect only macrophages/ microglia, which are thought to be less associated with acute inflammatory damage in stroke and do not correlate with infarct size, whereas neutrophil infiltration and MPO correlated well with infarct size (5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, several studies have reported the use of magnetic nanoparticles to identify inflammatory regions in stroke (4,(23)(24)(25). However, magnetic nanoparticles detect only macrophages/ microglia, which are thought to be less associated with acute inflammatory damage in stroke and do not correlate with infarct size, whereas neutrophil infiltration and MPO correlated well with infarct size (5).…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy is likely because experimental stroke is relatively homogeneous concerning size, territory, and etiology, and consequently inflammation is consistently elicited. However, human stroke is extremely heterogeneous (4), with different size and vascular territories involving different mechanisms. Therefore, there is a need to develop better inflammatory animal models and carefully select animals and individuals afflicted with stroke with a significant inflammatory component for antiinflammatory therapy and trials.…”
mentioning
confidence: 99%
“…Increased accumulation of SPIO in the microglia of the CNS in the case of disruption of the blood brain barrier (BBB) in tumorous CNS lesions [89] or inflammatory CNS lesions [92] which can be imaged with the help of T2w/T2*w MR sequences is observed in the case of the former applications.…”
Section: Cns Imagingmentioning
confidence: 99%
“…Systemic intravenous administration of ultrasmall superparamagnetic iron oxide nanoparticles for phagocytosis by activated blood-borne macrophages as a method to image the peripheral inflammatory response after stroke is one such application (Rausch et al, 2002;Wiart et al, 2007). However, evidence indicates this technique may not be so robust (Desestret et al, 2009;Henning et al, 2009), and more variability has been observed in the clinical setting Nighoghossian et al, 2007;Saleh et al, 2007). Therefore, albeit offering interesting insights into the poststroke inflammatory reaction, the current potential of these techniques for stroke outcome prediction is poor.…”
Section: Relaxometrymentioning
confidence: 99%